Factors affect wall slip: Particle size, concentration, and temperature - Chin, Ren Jie; Lai, Sai Hin; Ibrahim, Shaliza; Jaafar, Wan Zurina Wan (Kerschensteiner Verlag, 2018)
Concentrated suspensions are very complex in nature and exhibit non-Newtonian flow properties although the suspending fluid might behave as a Newtonian fluid. Among the interesting properties, wall slip will be the main focus of this study. The formation of wall slip layer adjacent to the solid boundary may lead to inaccurate measurement of rheological properties. So, the measured viscosity can be lower than the actual viscosity and thus a basic understanding on wall slip is critical. Concentration, particle size, and temperature are the factors affecting the wall slip mechanism. Therefore, this research study tends to study the relationship between the parameters (concentration, particle size, and temperature) and wall slip. The result shows that the slip velocity increases with shear stress under the conditions where (i) concentration decreases, (ii) particle size increases, and (iii) temperature increases. Two regression models considering the three parameters are proposed and can be used respectively as an alternative to predict slip velocity and true shear rate.